Dil-müzik İlişkisi Ekseninde Yapılanan Türk Halk Müziği Yöresel Ağız Özelliklerinin Fonetik Notasyonu - Demir, Gonca (Sosyal Bilimler Enstitüsü, 2011)
Müzik,Ağızlar, Dil ,Halk müziği, Ses bilgisi, Türk halk müziği, Türk lehçeleri

Music,Dialects , Language, Folk music, Phonetics, Turkish folk music, Turkish dialects
Phonetic notation of Turkish folk music local dialectic characteristics based on the axis of the relationship between language-music
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2011
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Social Sciences, 2011